Isotherm and Kinetic Adsorption of Cadmium (Cd) onto Biosorbent Made from Kepok Banana Peel (Musa Acuminata balbisian): The Effect of Activator Type and Biosorbent Dosage - Cundari*, Lia; Fanneze, Alna Livia; Arisma, Nanda Citra; Julian, Asha Aisha (Graduate School of Universitas Syiah Kuala, 2023)
The present study determined the isotherm and kinetics model of the cadmium adsorption process onto a biosorbent made from kepok banana peel (Musa Acuminata balbisian). The experiments were carried out in batch process, laboratories scale, room temperature, pH of Cadmium of 4, volume of Cd solution of 20 ml, and biosorbent size particle of 60 meshthe biosorbent produced using chemical activation method onto dry banana peel. The variation in this research was the type of activator (H3PO4 and H2SO4) and the biosorbent dosage (1, 1.5, and 2 g). The experimental data was used to calculate the Langmuir and Freundlich isothermKinetics analysis based on pseudo-first-order and second-order kinetics models. The best condition of the cadmium removal occurred at 90 minutes of contact time and 2 g dosage for H2SO4 and H3PO4 activators. Cadmium biosorption was in accordance with the Langmuir isotherm and pseudo-second-order kinetic model. The linear equation obtained is positive, with the maximum adsorption capacity and the affinity constant. Cadmium adsorption onto banana peel biosorbents followed the Langmuir adsorption isotherm pattern, so chemical adsorption occurred in this study. Cadmium adsorption kinetics onto biosorbent that activated with an acid activator of H3PO4 and H2SO4 followed the pseudo-second-order kinetic model. The best condition of the cadmium removal occurred at 90 minutes of contact time and 2 g dosage for H2SO4 and H3PO4 activators. Cadmium biosorption in this study was in accordance with the Langmuir isotherm and pseudo-second-order.